Women’s Psychological Resilience Against Intergenerational Trauma in Nguyen Phan Que Mai’s The Mountains Sing (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study examines the representations of intergenerational trauma and women’s psychological resilience in Nguyen Phan Que Mai’s The Mountains Sing. The relationships between a grandmother and her granddaughter, Dieu Lan and Huong, show that trauma may be passed down through generations along with the psychological resilience caused by historical trauma. This study investigates how family members’ psychological experiences are shaped by historical trauma caused by significant socio-political events, such as the Great Hunger, the Land Reform, and the Vietnam War. This study focuses on how important these events are in affecting family members’ dynamics throughout the story. Cathy Caruth’s trauma theory served as the theoretical foundation for the study, which employed a qualitative descriptive method through close reading of characterization, conversation, and descriptive passages. The results show that traumatic experiences and emotional suffering are passed down through generations through family narratives and inherited grief, while resilience is developed through the preservation of family continuity. The study concludes that women’s psychological resilience and intergenerational trauma are closely related because the same familial relationships that caused suffering also support the ability to persevere, adjust, and transform value for future generations.